Do Good, Better: Making a Difference in Global Oral Health - Donna Hackley; Christy Colburn; Jean Creasey (Taylor & Francis Group, 2024)
ABSTRACTShort-term mission trips have long served as a way for oral health professionals to "give back," using their abilities to address the heavy global burden of oral disease, a burden that disproportionately affects populations in low- and middle-income countries. These international volunteer programs may bring needed care to the communities they serve but can create challenges in ethical engagement, sustainability, and effectiveness. Currently, momentum is shifting away from the "clinical care elsewhere" model, where community context, relationship building, monitoring, and sustainability can be lacking, and moving toward approaches that focus on community collaboration, leadership, education, and advocacy. This paper aims to help clinicians evaluate their current and future short-term volunteer work through a new paradigm.